Garcinia drying using mixed-mode solar dryer technique: Drying kinetics, mathematical modeling and quality characteristics - Eleeyah Saniso; Lutfee Sueni; Muhammadkhoiri Hayibaka; Somakorn Chaiwarakorn; Abedeen Dasaesamoh; Huseng Chaidana (Case Studies in Thermal Engineering)
Fresh Garcinia, with a high MC at 725.9 ± 36.3 % d.b, requires a reduction in its MC for storage before processing. This study aimed to evaluate the drying kinetics, mathematical models, and quality of dried sliced Garcinia using MMSD. The sliced Garcinia is dried using a MMSD system under natural airflow and airflow at 0.5, 1.0, and 0.5 m/s (trays switched), as well as OSD during daytime from 8.00 a.m. to 4.00 p.m. The results indicated that drying sliced Garcinia using MMSD at 0.5 m/s of airflow with the tray switched reduced the MC to 20–25 % d.b. within 12 h. The drying time was 25 % shorter compared to OSD. The Midilli & Kucuk, two-term exponential and logarithmic models exhibited the best fit for MMSD and OSD drying. The Deff of the sliced Garcinia dried by OSD and MMSD under various drying airflow was from 4.14 × 10−6 to 7.98 × 10−6 m2/h. The sliced Garcinia dried by MMSD exhibited an apparent golden-yellow color, while those dried by OSD exhibited an apparent reddish-yellow color. Furthermore, the overall polyphenols, phenolics, and flavonoids content in dried sliced Garcinia using MMSD and OSD showed an insignificant difference.